Intestinal Radiation-Induced Stricture Favours Small Bowel Obstruction by Phytobezoar: Report of a Case - Alessandra Quercioli; Franco Dallegri; Luciano Ottonello; Fabrizio Montecucco; Giacomo Borgonovo (Gastroenterology Research and Practice)
Bezoars represent the fifth most frequent cause of acute small bowel obstruction. Phytobezoar is the most common type of bezoar. It is a concretion of undigestible fibers derived from ingested vegetables and fruits. We report a case of a woman with a 1-year history of recurrent epigastric and periumbilical abdominal pain with intermittent vomiting caused by phytobezoar of the terminal ileum. After careful investigation of the case and review of literature, we identified the factor involved in bezoar formation as radiation-induced ileal stenosis due to previous treatment for a pelvic tumour. This report provides evidence to consider phytobezoar as a possible cause of small bowel obstruction in patients previously treated with abdominal radiotherapy.